2017
DOI: 10.3389/fncom.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Absence Seizures through the Deep Brain Stimulation to Thalamus Reticular Nucleus

Abstract: Deep brain stimulation (DBS) can play a crucial role in the modulation of absence seizures, yet relevant biophysical mechanisms are not completely established. In this paper, on the basis of a biophysical mean-field model, we investigate a typical absence epilepsy activity by introducing slow kinetics of GABAB receptors on thalamus reticular nucleus (TRN). We find that the region of spike and slow-wave discharges (SWDs) can be reduced greatly when we add the DBS to TRN. Furthermore, we systematically explore h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Neural field models (Taylor et al, 2014; Wang and Wang, 2017) have been successfully applied to investigate the effect of stimulation on the SWD of absence seizures in epilepsy. As seen in Figure 2, the thalamocortical loop consists of cortical subsystem and thalamic subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…Neural field models (Taylor et al, 2014; Wang and Wang, 2017) have been successfully applied to investigate the effect of stimulation on the SWD of absence seizures in epilepsy. As seen in Figure 2, the thalamocortical loop consists of cortical subsystem and thalamic subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent follow-up study, Wang et al [ 64 ] employed a mean-field modeling approach and found that the slow kinetics of GABA B receptors on thalamus reticular nucleus (TRN) lead to spike-wave discharges (SWDs). The deep brain stimulation (DBS) was applied to the TRN which helped in eliminating the SWDs.…”
Section: Discussionmentioning
confidence: 99%
“…Intensively developed investigations of genetic forms of absence seizures performed during the last decades [10][11][12][13][14]. Calcium channel deteriorations may underlay such hyperactive state of neurons within the CTC networks due to an with the two-phase effects of vigabatrin upon SWD [29] and with the suppression of SWD caused by DBS of RT [30].…”
Section: Introductionmentioning
confidence: 99%
“…Searching for alternative therapy of not-responsive AS targets for DBS proved promising [35]. Among others, thalamic structures are the first line of such targets [30,35,36], while the cerebellum is almost beyond the scope of interest. Hence, our investigation aimed to observe the specificity evolution of interictal penicillin-induced cortical focal activity, emphasizing slow-wave characteristics, and spikes PPC under paleocerebellar electrical stimulation (ES).…”
Section: Introductionmentioning
confidence: 99%